2021
DOI: 10.21608/jssae.2021.153316
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Foliar Application with Nano-Micronutrients and Organic Fertilization on Snap Bean under Sandy Soil Condition

Abstract: Nanotechnology presents brilliant agricultural products, which may be an achievement in addressing many common economic and ecological issues. Nano-fertilizers show special characters which do not exist in their conventional counterparts. So; this work conducted out during 2019 and 2020 seasons to investigate the effects of three forms of micronutrient Fe + Zn in foliar way (nano, EDTA and sulfate) under organic fertilization (without, chicken manure and FYM) on vegetative growth, physical, chemical and qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…The results show that the combined application of Fe + Zn NPs and organic fertilizer had significant effects on plant growth and improved pods’ physical and nutritional quality. The analysis of soil at the end of the experiment showed that they also improved the quality of soil and made it more fertile [ 152 ]. The researchers of Iraq combined biofertilizer with the nano-element mixture and analyzed their effect on two varieties of P. vulgaris .…”
Section: Current Scenario Of Nanobiofertilizer Research and Applicationsmentioning
confidence: 99%
“…The results show that the combined application of Fe + Zn NPs and organic fertilizer had significant effects on plant growth and improved pods’ physical and nutritional quality. The analysis of soil at the end of the experiment showed that they also improved the quality of soil and made it more fertile [ 152 ]. The researchers of Iraq combined biofertilizer with the nano-element mixture and analyzed their effect on two varieties of P. vulgaris .…”
Section: Current Scenario Of Nanobiofertilizer Research and Applicationsmentioning
confidence: 99%